2011
DOI: 10.1007/s00167-011-1395-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of range of motion 2 years after mobile-bearing total knee arthroplasty: PCL-retaining versus PCL-sacrificing

Abstract: This study showed the effects of retention of the PCL and the degree of its functional recovery on postoperative ROM for the two prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…A previous study demonstrated that the ROM 24 months after TKA could be predicted from the ROM after 6 months [17] and the ROM collected at 6 months was sufficient for an analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the ROM 24 months after TKA could be predicted from the ROM after 6 months [17] and the ROM collected at 6 months was sufficient for an analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the interval between preoperative and postoperative knee flexion measurements varied between 6 and 114 months owing to study design, and this may have affected our results. However, we showed that with the current prosthetic design, knee ROM values after 24 months can be predicted statistically from the ROM values at 3 months [7]. Additionally, the average change in maximum knee flexion from 6 months to 3 years postoperatively was reported to be only 2.8° [20].…”
Section: Discussionmentioning
confidence: 99%
“…The TKAs being evaluated were performed at a mean of 23 months after the index TKA (range, 6–114 months). One surgeon (YI) performed all the TKAs using a standardized technique, including the necessary soft tissue release for proper balance; the surgical technique and rehabilitation protocol are described in detail in a previous report [7]. In all knees, the femoral components were fixed without cement and the tibial components were fixed with cement.…”
Section: Methodsmentioning
confidence: 99%
“…Second, this study neither evaluated the clinical significance nor compared the other anatomical landmarks of malrotation of the tibial component relative to the TEA in both implant designs. However, no significant differences in the clinical results [44] of knee arthroplasties using both implant designs were found in author's previous studies using the same procedure performed by the same surgeon (Y.I.). Third, it is possible that maximization of tibial surface coverage might not have been undertaken because priority was always given to correct tibial rotational positioning rather than the coverage.…”
Section: Discussionmentioning
confidence: 84%